Evaluation method of privacy protection effect based on multi-layer fuzzy comprehensive evaluation - Yihan YU; Yu FU; Xiaoping WU (网络与信息安全学报)
Aiming at the problem that the evaluation of the privacy protection effect from a single data level cannot describe the overall privacy protection effect of the network environment,with the help of the fuzzy comprehensive evaluation method,the privacy protection effect influencing factors were condensed from the entire life cycle of the data.According to the data privacy differences,the factors and block weights were determined,and the overall calculation results of the overall privacy protection effect of the network environment were obtained.Case analysis shows that the proposed method is feasible and effective.